Marketing Location as a Key Determinant for Inflow of Direct Investments into Bosnia and Herzegovina - Smajlović, Ermina; Kamarić, Alma; Ninić, Boro (International Journal of Management and Sustainability, 2014)
The analysis of realized investments of individual regions and sub-regions opens up a question of relevant factors upon which foreign investors make decisions about investments into a certain location. Therefore, the objective of this paper is the theoretical elaboration of starting factors and determinants of foreign capital attractions, as well as, the observation of effects of marketing location on investment realisation. Identification of key motives, as well as the determination of the level of their significance in realisation of foreign investments into Bosnia and Herzegovina (hereinafter B&H), is necessary in order to define the effect of incentive measures for investment realisation. The results, presented in this paper, are gathered through primary research of companies formed by realisation of foreign investments into B&H (written structured survey). The data has been gathered on basis of a simple random sample made up of 30 surveyed, that is, 30 companies from B&H territory that occurred as a result of the realisation of foreign direct investments (hereinafter FDI) in our country. The research results show that B&H, regardless of its unstable political situation, poor investment climate, complex government structure, has an exceptional potential for the increase of FDI inflow, and that it is still attractive to foreign investors due to its technical-technological know-how, its natural resources, as well as is qualified and educated labour force.